COMPARATIVE ANALYSIS OF INDO-US ELECTORAL SYSTEM: EXPLORING CONVERGENCES AND DIVERGENCES IN THE ERA OF SOCIAL MEDIA - Chadha, Nishtha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the impact of technological advancements in media on the strategies employed by political leaders to communicate with the public, and to examine how these changes influence the voting public’s perception and reception of political messages with a comparative analysis between India and the USA. In this regard this study employed a qualitative analysis method for the research by utilizing content analysis and case study methodology. A systematic examination of media coverage and political leaders’ communication strategies across various platforms was conducted and an in-depth analyses of specific political campaigns or events to illustrate the impact of technological advancements in media on political communication and public engagement. The research highlights the interconnectedness of media and electoral politics, showcasing how social media platforms have revolutionized traditional modes of political engagement. The study reveals that social media has enabled two-way communication between voters and political leaders, amplifying marginalized voices and transforming political discourse. However, this shift also presents challenges, including the spread of disinformation and difficulties navigating social media . The findings emphasize the significance of social media in shaping electoral politics, influencing political participation, engagement, and the democratic process. As social media evolves, addressing its challenges and threats is crucial to ensuring informed citizenship and democratic values.